A novel MVA vectored Chikungunya virus vaccine elicits protective immunity in mice. - James Weger-Lucarelli; Haiyan Chu; Matthew T Aliota; Charalambos D Partidos; Jorge E Osorio (Public Library of Science (PLoS), 2014)
Chikungunya virus (CHIKV) is a re-emerging arbovirus associated with febrile illness often accompanied by rash and arthralgia that may persist for several years. Outbreaks are associated with high morbidity and create a public health challenge for countries affected. Recent outbreaks have occurred in both Europe and the Americas, suggesting CHIKV may continue to spread. Despite the sustained threat of the virus, there is no approved vaccine or antiviral therapy against CHIKV. Therefore, it is critical to develop a vaccine that is both well tolerated and highly protective.In this study, we describe the construction and characterization of a modified Vaccinia virus Ankara (MVA) virus expressing CHIKV E3 and E2 proteins (MVA-CHIK) that protected several mouse models from challenge with CHIKV. In particular, BALB/c mice were completely protected against viremia upon challenge with CHIKV after two doses of MVA-CHIK. Additionally, A129 mice (deficient in IFNα/β) were protected from viremia, footpad swelling, and mortality. While high anti-virus antibodies were elicited, low or undetectable levels of neutralizing antibodies were produced in both mouse models. However, passive transfer of MVA-CHIK immune serum to naïve mice did not protect against mortality, suggesting that antibodies may not be the main effectors of protection afforded by MVA-CHIK. Furthermore, depletion of CD4(+), but not CD8(+) T-cells from vaccinated mice resulted in 100% mortality, implicating the indispensable role of CD4(+) T-cells in the protection afforded by MVA-CHIK.The results presented herein demonstrate the potential of MVA to effectively express CHIKV E3-E2 proteins and generate protective immune responses. Our findings challenge the assumption that only neutralizing antibodies are effective in providing protection against CHIKV, and provides a framework for the development of novel, more effective vaccine strategies to combat CHIKV.